FORMATION OF ACCOUNTING POLICIES FOR CROP PRODUCTION COSTS - Грищук, Ганна (SWorldJournal, 2022)
The paper highlights the organizational and methodological issues of forming the accounting policy of agricultural enterprises in terms of cost accounting. It has been established that expenses are the object of accounting policy, as there are alternative